Structural and optical properties of ZnO–SnO2 mixed thin films deposited by spray pyrolysis - Thanihaichelvan, T.; Haseeb, A.S.M.A.; Sabri, M.F.M. (Elsevier, 2014)
Nanocrystalline ZnO–SnO2 mixed thin filmswere deposited by the spray pyrolysis technique at various substrate temperatures during deposition. The mixed films were prepared in the range of 20.9 at.% to 73.4 at.% by altering the Zn/(Sn + Zn) atomic ratio in the starting solution. Morphology, crystal structures, and optical properties of the films were characterized by field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and ultraviolet–visible and photoluminescence (PL) spectroscopy. XRD analysis reveals that the crystallinity of the Sn-rich mixed thin films increases with increasing substrate temperatures. FESEM images show that the grain size ofmixed thin films is smaller compared to that of pure ZnO and SnO2 thin films. A drop in the thickness and optical bandgap of the film was observed for films fabricated at high temperatures,which coincidedwith the increased crystallinity of the films. The average optical transmission of mixed thin films increased from 70% to 95% within the visible range (400–800 nm) as the substrate temperature increases. Optical bandgap of the films was determined to be in the range of 3.21–3.96 eV. The blue shift in the PL spectra from the films was supported by the fact that grain size of the mixed thin films is much smaller than that of the pure ZnO and SnO2 thin films. Due to the improved transmission and reduced grain size, the ZnO–SnO2 mixed thin films can have potential use in photovoltaic and gas sensing applications.
Keywords: Zinc oxide; Mixed thin film; Tin oxide; Spray pyrolysis